2013
DOI: 10.1177/1479164113498083
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in albuminuria in patients with type 2 diabetes after laparoscopic adjustable gastric banding

Abstract: Purpose: To determine the effects of laparoscopic adjustable gastric banding (LAGB) on albuminuria in patients with obesity, type 2 diabetes mellitus (T2DM) and established diabetic nephropathy. Methods: A retrospective analysis of clinical records from a tertiary diabetes service identified obese patients with T2DM who had micro-or macroalbuminuria prior to LAGB surgery. Clinical data from follow-up appointments including albuminuria were analysed. Results: A total of 23 T2DM patients were included in the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
(72 reference statements)
1
7
0
Order By: Relevance
“…Surgery performed included Sleeve Gastrectomy (SG), Roux-en-Y gastric bypass (RYGB) and Lap-Adjustable Gastric Bypass (LAGB). Our results are similar to earlier retrospective studies on effects of BS on DN, such as Zhang et al’s 15 RYGB, Stephenson et al’s 16 LAGB or Iaconelli et al’s 17 prospective study on bilio-pancreatic diversion (BPD) surgery. All three studies showed improvement of DN post surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Surgery performed included Sleeve Gastrectomy (SG), Roux-en-Y gastric bypass (RYGB) and Lap-Adjustable Gastric Bypass (LAGB). Our results are similar to earlier retrospective studies on effects of BS on DN, such as Zhang et al’s 15 RYGB, Stephenson et al’s 16 LAGB or Iaconelli et al’s 17 prospective study on bilio-pancreatic diversion (BPD) surgery. All three studies showed improvement of DN post surgery.…”
Section: Discussionsupporting
confidence: 91%
“…Stephenson et al [35] studied 3-year outcomes after bariatric surgery in 23 patients with T2DM and baseline albuminuria. Mean weight loss was 17 % over the period.…”
Section: Bariatric Surgery-retrospectivementioning
confidence: 98%
“…Due to their outcomes could not be combined with other studies, 2 studies [ 41 , 48 ] were excluded from meta-analysis. 14 studies of 1186 patients with dichotomous data [ 21 , 23 , 24 , 26 , 27 , 29 , 32 34 , 38 , 42 , 43 , 45 , 51 ] and 10 studies of 930 patients with continuous data [ 24 , 25 , 29 , 33 , 36 , 37 , 46 , 47 , 49 , 50 ] were included in the meta-analysis of albuminuria and proteinuria. There were only 5 studies of 184 patients [ 25 , 26 , 28 , 40 , 44 ] in the review of CKD II.…”
Section: Resultsmentioning
confidence: 99%